Proceedings of the Thirty-Second International Joint Conference on Artificial Intelligence 2023
DOI: 10.24963/ijcai.2023/523
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Transformer for Scalable Graph Learning

Abstract: Graph Transformer is gaining increasing attention in the field of machine learning and has demonstrated state-of-the-art performance on benchmarks for graph representation learning. However, as current implementations of Graph Transformer primarily focus on learning representations of small-scale graphs, the quadratic complexity of the global self-attention mechanism presents a challenge for full-batch training when applied to larger graphs. Additionally, conventional sampling-based methods fail to capture nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Observe that, empirically, we mainly focus on a maximal hierarchy level of K = 1. This is in line with related works (Zhang et al 2022;Zhu et al 2023) and showed good performance in our evaluation.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Observe that, empirically, we mainly focus on a maximal hierarchy level of K = 1. This is in line with related works (Zhang et al 2022;Zhu et al 2023) and showed good performance in our evaluation.…”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, as the K increases, there is no significant improvement in the results. This might explain why we chose K = 1 in line with related works (Zhang et al 2022;Zhu et al 2023).…”
Section: Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…Clustering based GTs. Orthogonally, several recent works use hierarchical clustering or partitioning to perform global attention on the coarsened or super nodes [189,190]. However, the coarsening step remains intractable for very large Local Inductive Bias: A node's local neighborhood connectivity presents a rich source of information that is essential to utilize even in a large graph setting.…”
Section: Introductionmentioning
confidence: 99%